Investigação sobre o trabalho de professores de matemática da rede pública estadual de Santa Maria (RS) que possuem alunos incluídos em suas salas de aula - Cocco, Patrícia Manfio (2017)
The present work was developed in the Postgraduate Program in Mathematics Education and Physics Teaching (PPGEM & EF) of the Federal University of Santa Maria (UFSM) and inserted in the line of research Teaching and Learning of Mathematics and its Philosophical, Historical and Epistemological Foundations. Based on interviews with the pedagogical advisor of the 8ª Regional Education Coordination (8ª CRE), responsible for the Special Education sector, with teachers of Mathematics from state schools of Basic Education and the analysis of official documents of the Brazilian legislation on Special Education and Inclusive Education, curricula and pedagogical projects of undergraduate courses in Mathematics, this research aimed to investigate how these Mathematics teachers organize their classes for teaching in classes that have students included. For the data collection, semi-structured interviews were carried out with five Mathematics teachers from the state public school system who work or have already worked with students included in the regular education and with the pedagogical advisor responsible for the Special Education sector of the 8ª CRE. We used as a theoretical methodological reference for conducting these interviews Oral History, based on the ideas of José Carlos Sebe Bom Meihy (1996) and, mainly, the works developed by the Oral History and Mathematics Education Research Group, coordinated by Antonio Vicente Marafioti Garnica (2005, 2007, 2011, 2013). The analysis of the interviews was performed - according to the work carried out by Maria Edneia Martins-Salandim - in two moments: analysis of singularities and analysis of convergences. In the analysis of singularities we try to record what is characteristic of each deponent in his narrative, its peculiarities and its particularities. In the analysis of convergences we seek to confront the narratives of our deponents with what is written in the official documents of the legislation on Special Education and Inclusive Education and with the grades and pedagogical projects of the degree courses in Mathematics of the institutions where the teachers interviewed concluded the course Training. For this, we list three units of analysis: initial training, continuing training and work with included students. We emphasize, from the analysis carried out, that the Mathematics teachers interviewed consider that the work carried out with students included in regular education is hard work and difficult to be developed, since they did not receive orientation in the initial training course to work with these students. In addition, they have taken part in a few continuing education courses related to this topic, and the 8ª CRE does not provide guidelines for this work that be aimed at teachers in areas other than Special Education.